Labour market returns to higher education in Vietnam - Tinh Doan; Philip Stevens (Economics: The Open-Access, Open-Assessment E-Journal, 2011)
This paper employs the Ordinary Least Squares, Instrumental Variables and Treatment Effect models to a new dataset from the Vietnam Household Living Standards Survey (VHLSS) to estimate return to four-year university education in 2008. Our estimates reveal that income premium of four-year university education is about 97 percent above that of high school education, and robust to the various estimators.
Keywords: C31; J31; O15; 330; Bildungsertrag; Studium; Arbeitsmarkt; Vietnam